6-(-5+4i)-(-13-I)=0

Simple and best practice solution for 6-(-5+4i)-(-13-I)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(-5+4i)-(-13-I)=0 equation:


Simplifying
6 + -1(-5 + 4i) + -1(-13 + -1I) = 0
6 + (-5 * -1 + 4i * -1) + -1(-13 + -1I) = 0
6 + (5 + -4i) + -1(-13 + -1I) = 0
6 + 5 + -4i + (-13 * -1 + -1I * -1) = 0
6 + 5 + -4i + (13 + 1I) = 0

Reorder the terms:
6 + 5 + 13 + 1I + -4i = 0

Combine like terms: 6 + 5 = 11
11 + 13 + 1I + -4i = 0

Combine like terms: 11 + 13 = 24
24 + 1I + -4i = 0

Solving
24 + 1I + -4i = 0

Solving for variable 'I'.

Move all terms containing I to the left, all other terms to the right.

Add '-24' to each side of the equation.
24 + 1I + -24 + -4i = 0 + -24

Reorder the terms:
24 + -24 + 1I + -4i = 0 + -24

Combine like terms: 24 + -24 = 0
0 + 1I + -4i = 0 + -24
1I + -4i = 0 + -24

Combine like terms: 0 + -24 = -24
1I + -4i = -24

Add '4i' to each side of the equation.
1I + -4i + 4i = -24 + 4i

Combine like terms: -4i + 4i = 0
1I + 0 = -24 + 4i
1I = -24 + 4i

Divide each side by '1'.
I = -24 + 4i

Simplifying
I = -24 + 4i

See similar equations:

| 1.6z+18=2z-2 | | (y-11)+(y+8)=6y | | 3(r+1)-2(3-2r)-3(3-r)=2(r+5)-4 | | =60ln(x+1) | | (3+2i)-(5-7i)=0 | | 35n-4=66 | | 3w^2=-27w | | 8X+30=10X | | -5(z-9)(-z-3)=0 | | 5z+16=4z-10 | | 2X-30-X=30-4X | | -4z(z-3)(z-9)=0 | | 15x-52=5x+18 | | x^2+10x-73= | | x^2+10x-73= | | 10X=9+4X+51 | | x^2+10x-73=0 | | (y-4)(y+8)=0 | | x^2+6x-73=0 | | 17x-(6x-4)=48 | | 2(x-18)=-2 | | -4x+66=3x+38 | | 4+3*2=14 | | 3x-10+5x+10=180 | | -3y-3=2-2y | | x+x^2=25.862 | | y+1x+0=2 | | 7x+11=3x+79 | | -6v-6(2x-4)=84 | | 7*x^2-11-30=0 | | 2x^3-9x^2-1=0 | | 7d-r(d+8)=-8 |

Equations solver categories